Genetic Relationship amongst Marica, Kacang Goat and Capra species - Rosdiana Ngitung; Herry Sonjaya; Syamsuddin Hasan; Wempie Wempie (International Journal of Agriculture System, 2013)
Marica goat is an endemic species that can be found only in South Sulawesi, Indonesia. It has been reported by the FAO as endangered species because its number of population has been significantly decreased. Domestication by local people has been done by cultivating them with Kacang goat that leads to an interbreeding process. Conservation of the goats must be done immediately due to its rapidly decreasing population. However, accurate identification and quantification of the goat by DNA analysis is highly important. The objective of this study is to determine the differences amongst marica, kacang and Capra hircus, C. caucasica and C. falconeri from the GenBank. The sequence of the mitochondrial DNA (mtDNA) at d-loop region of 30 Marica goats and five Kacang goats from three districts in South Sulawesi were investigated. Their nucleotide sequences were compared with the sequence of the GenBank’s Capra sp and were analyzed using Dendogram neighbor joining tree. The results showed that there were a few nucleotide differences between some Marica and Kacang goat that were located at 20, 840 and 980bp. In addition, both nucleotides sequence have short genetic distance compared to C. hircus. However, comparing with other Capra sp, the distance was significantly far. Meanwhile, according to the dendogram, it was found that all Goats and Capra sp came from the same ancestral lineage. It can be concluded that Marica and Kacang goats could be very closely related with C. hircus but they were different from the C. caucasica and C. falconeri.